Comparing the circulating immune profile of women with and without recurrent implantation failure: a systematic review and meta-analysis - Bhatt, Daxina; Alebrahim, Yousef; Shahzad, Abdullah; Mohiyiddeen, Lamiya; Mann, Elizabeth (Frontiers in Immunology, 2025)
IntroductionEmbryo implantation is a complex process requiring a tightly regulated immunological dialogue at the maternal-embryonic interface. Disruptions in this dialogue, including alterations in immune cell function and cytokine production, have been implicated in implantation failure. This systematic review and meta-analysis aimed to quantitatively compare immune-related soluble mediators in the peripheral blood of women with unexplained recurrent implantation failure (RIF) and fertile controls.MethodsThis systematic review was conducted according to PRISMA principles. A comprehensive search was conducted across Embase, MEDLINE, and the Cochrane Central Register of Controlled Trials. The primary outcome measure was the differential concentration of immune analytes in blood and tissue samples between women with recurrent implantation failure and fertile controls. Meta-analysis was performed for five peripheral blood cytokines (IFN-γ, IL-4, TNF-α, IL-2, IL-6).ResultsSome 12 studies reporting on 1483 patients met the final inclusion criteria for the review. The meta-analysis revealed a statistically significant difference only for Interleukin-4 (IL-4), which was lower in women with RIF compared to controls (MD -0.0298, 95% CI: -0.0436 to -0.0159, p < 0.0001). No significant differences were found for IFN-γ, TNF-α, IL-2, or IL-6. Individual studies reported varied associations for other analytes, including lower levels of Angiopoietin-2, MMP-7, VEGF, FGF1, Glycodelin A, and MUC1, and higher levels of PDGF, TGF-β isoforms and CCL2, IL-2 in RIF cohorts. The overall certainty of the evidence was rated as low, due to concerns about study quality and heterogeneity in RIF definitions, control group selection, and laboratory methodologies.ConclusionThe review highlights that immune dysregulation is associated with RIF. In particular, IL-4 may play an important role although the clinical relevance of the small, measured difference is unclear. There is a need for international consensus on RIF definition, standardised methodological protocols, and large-scale prospective studies to validate potential immune biomarkers. Currently, there is insufficient evidence to support the routine use of peripheral blood cytokine levels as diagnostic markers for RIF or to guide immunomodulatory treatment.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier PROSPERO 42024577277.